Pengembangan Aplikasi Manajemen Rekrutmen Karyawan Menggunakan Metode Profile Matching - Hery, Hery; Christopher, Raphael; Widjaja, Andree E.; Suryasari, Suryasari (Universitas Nusantara PGRI Kediri, 2019)
Human Resources (HR) is one of the important aspects in the company, because it will manage many aspects such as technology, resources, and capital, therefore the process of hiring and allocating training is important in the company. Human Resource Departement (HRD) is responsible for recruiting new employees and developing training programs to equip employees or prospective employees. The Recruitment process consist of three steps: CV gathering, psychotest work, and interview). In PT. XYZ recruitment process is done manually,Therefore an application is required that can support the decision-making process in the employee recruitment process that can analyze the appropriate training for prospective employees. Employee recruitment applications development and allocation of employee training using the System Development Life Cycle (SDLC) system development methodology. For employee training allocation system with profile matching method. The Final result from this research is an application that could support HRD in recruitment process and training allocation.